2011
DOI: 10.1155/2011/353878
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Molecules of Mesenchymal Stem Cells for Hematopoietic Stem Cell Niche

Abstract: Hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs) are both adult stem cells residing in the bone marrow. MSCs interact with HSCs, they stimulate and enhance the proliferation of HSCs by secreting regulatory molecules and cytokines, providing a specialized microenvironment for controlling the process of hematopoiesis. In this paper we discuss how MSCs contribute to HSC niche, maintain the stemness and proliferation of HSCs, and support HSC transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 100 publications
1
53
0
1
Order By: Relevance
“…Accordingly, the expression of two cytokines, G-CSF and vascular endothelial growth factor were significantly down-regulated in Dicer1-KD MSC. These molecules are involved in the regulation of hematopoiesis, 45,46 suggesting that their deregulation contributes to the impaired support of hematopoiesis characteristic of Dicer1-KD MSC. It is worth mentioning that the level of G-CSF expression has been reported to be decreased in MDS-MSC.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the expression of two cytokines, G-CSF and vascular endothelial growth factor were significantly down-regulated in Dicer1-KD MSC. These molecules are involved in the regulation of hematopoiesis, 45,46 suggesting that their deregulation contributes to the impaired support of hematopoiesis characteristic of Dicer1-KD MSC. It is worth mentioning that the level of G-CSF expression has been reported to be decreased in MDS-MSC.…”
Section: Discussionmentioning
confidence: 99%
“…They can differentiate along multiple lineages and exhibit significant expansion capability in vitro. Co-transplantation with MSCs improves engraftment of HSCs after autologous intra-bone marrow transplantation [3]. MSCs are also considered useful as vehicles for emerging cell and gene therapies in the field of tissue engineering [4].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are also considered useful as vehicles for emerging cell and gene therapies in the field of tissue engineering [4]. Recently it has been postulated that MSC provide the conducive microenvironment for HSCs and thus maintain the stemness and proliferation of HSCs and support HSC transplantation [3].…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have been demonstrated to support long-term growth of HSCs hematopoietic stem cells and maintain hematopoietic and skeletal homeostasis [2]. Previous studies showed MSCs transplantation resulted in improvement of diabetes conditions, such as reducing blood glucose levels [3][4][5], partially because of the immunosuppressive effects of MSCs on T cells, increasing pancreatic islet β cell mass, preventing of β cell death [6] and promoting islet regeneration [7].…”
Section: Introductionmentioning
confidence: 99%